DETECTION OF GIARDIA INFECTION IN DOGS OF BASRAH CITY - Ali Naser; Israa abdul wadood (Basrah Journal of Veterinary Research)
The present study was conducted to determine detect the infection rate of Giardiasis in local canine breeds of Basrah, Iraq. Two hundred and twenty-five (225) fecal samples were collected from dogs of both sexes from March to October 2016. Suspected animals either asymptomatic (56.7%) or symptomatic (43.3%) the suspected dogs show different clinical signs such as diarrhea (6.66%), pasty feces (13.33%), steatorrhea (8.00%), anorexia (10.66%), emaciation (15.55%) and vomiting (0.88%). Diagnosis of Giardia spp was done on basis of microscopic examination which detects Giardia cyst and trophozoite with infection rate (40 %), moreover, it was confirmed by ELISA technique(Giardia-specific antigen) to detect (75.55%) was infected with G. lamblia with a high infection rate comparison with microscopic examination. It had been shown that high infection rate (43.75%) was detected in March than the lowest in July (34.78%). Moreover infection with Giardia was found more common at (1 day to 6 months) of age; furthermore, females show infection rate more males. It has been concluded that giardiasis affected canine of Basrah city lead to substantial effect, therefore animals must be screened periodically.